Agro-industrial development and sustainability in Bangladesh-A study (International Journal of Agricultural Research, Innovation and Technology, 2016)
A study was conducted to know the current state of development sustainability of the agroindustrial sector in terms of its product diversity, export volume, export value, destination of the product by region and country. A structured questionnaire was prepared to do the random sampling survey and focused group discussion also held with the relevant stakeholder in agro-industrial sphere. The study revealed that in terms of value, the highest exported agro processed product is spices 21.46 million US$ (25%) and in terms of weight, the highest exported agro processed product is drinks (26735 ton). It is investigated that 81% of Bangladesh agro processed product goes to Asian market which value is US$ 70.13 million. In terms of export value, the major destination of Bangladesh agro-processed product is Kingdom of Saudi Arabia(KSA) which amount is 20.2 million US$. In terms of export in weight, the major destination of Bangladesh agro-processed product is India (24372.88 metric ton).Int. J. Agril. Res. Innov. & Tech. 5 (2): 37-43, December, 2015